Simulasi Uji Beban Statis dengan Variasi Jenis Konstruksi pada Kekuatan Produk Stool Kayu Persegi - Rahmat, Bahtiar (Tadulako University, 2026)
Furniture products still been one of the export commodities that required attention. Contributing a value of more than USD 1 billion, consistency in maintaining the quality of furniture products needed to be improved. The construction or joints in furniture products had been the parts most prone to defects, cracks, or even fractures due to external forces, both during testing and usage. Prototype product testing required more time and resources. As a result, a method had been developed to obtain strength test data without creating a prototype, known as the Finite Element Analysis (FEA) method. The objective of this study is to measure the joint strength of a stool assembled with three types of construction: dowel pin, biscuit lamello, and open tenon joints. The external load had been adjusted according to the Indonesian National Standard (SNI) in terms of force position, magnitude, and direction. The results of the static load simulation shown that the application of all three types of construction had been able to withstand an external load of 1100 N effectively. The maximum von mises stress, which had been 9.647 MPa, had still been far below the material's yield stress of 41.2 MPa. Additionally, the maximum deflection and strain had only been 0.198 mm and 8.640e-04, respectively, in the product with biscuit lamello construction. The dowel pin construction had also produced a maximum stress of 6.031 MPa, a strain of 4.247e-04, and a maximum deflection of 0.170 mm, with a safety factor of 7.11. However, overall, the application of open tenon construction had been more recommended, as it had achieved the best safety factor of 13.630, with the maximum stress experienced by the stool being only 3.670 MPa.